The Ølby Woman:: A Comprehensive Provenance Investigation of an Elite Nordic Bronze Age Oak-Coffin Burial - Reiter, Samantha Scott; Frei, Karin Margarita; Nørgaard, Heide Wrobel; Kaul, Flemming (Danish Journal of Archaeology, 2019)
The Early Nordic Bronze Age oak coffin burials include some of Europe’s best preserved human remains. Although traditional typological examinations thereof have not always found clear foreign references, recent provenance investigations from Egtved and Skrydstrup suggest that the two women were of non-local provenance. In order to investigate potential mobility patterns and how these might or might not be related to the archaeological evidence, we conducted comprehensive multi-analytical investigations on the Ølby Woman, another key female oak coffin burial. Her grave included large metal items, the remains of a corded skirt and a glass bead recently identified as of Egyptian origin. Strontium isotope analyses of the dental enamel of Ølby’s first, second and third molars investigate her provenance and potential mobility through childhood. Furthermore, we conducted lead isotope analyses and craft technical analyses of her belt plate and sword/dagger. Our results reveal that the Ølby female’s strontium isotope signatures fall within the local baseline, suggesting that she was of local origin. The metal provenance studies and craft technical studies of the belt plate and sword suggest that the objects were manufactured in Scandinavia, while the raw materials for each item were imported from different places in Europe.